Dayah Leaders' Perceptions of the Aceh Local Party's Political Communication Methods (Partai Pas Region Lhokseumawe) - Muntasir A. Kadir; Muhibuddin Alamsyah; Muttaqien; Yusfriadi Abda (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Elections in Indonesia are a political party that is very interesting to study and look forward to because they arise from various aspects and social groups in Indonesia. In Aceh, the intersection between religion and politics is very pronounced, including the Dayah which plays a major role as one of the influential places in Aceh in both fields. It is important to understand how the Dayah leadership views and engages in local parties' political communication methods, which is crucial to understanding the broader socio-political landscape in Aceh. This research investigates the perceptions of Dayah leaders regarding political communication methods used by local Acehnese parties, namely the PAS party in the Lhokseumawe region. Dayah educational institutions which are deeply rooted in Aceh's socio-political landscape also play an important role in shaping public opinion and influencing political dynamics. Through qualitative research methods, this research explores the views of the Dayah leadership and interacts with the political communication strategy of the PAS party in the Lhokseumawe region. This research also highlights the dynamics between religious authority and political involvement in Acehnese society.